ANALISIS MANAJEMEN RISIKO PENERAPAN BELAJAR ONLINE (STUDI KASUS: SD NEGERI 12 CAWANG) - Berty Octavia Nainggolan; Indra Gunawan (Unitri Press, 2021)
This study was intended to analyze the impact of the Covid-19 pandemic on face-to-face learning and the implementation of risk management on the effectiveness of online learning. By conducting a case study at SDN 12 Cawang, East Jakarta, the researcher argued that the case that occurred at SDN 12 Cawang can be a barometer of the impact of the Covid 19 pandemic on face-to-face learning and the implementation of risk management for online learning at the elementary school level holistically. The existence of the Distance Learning (PJJ) policy changed the technical learning from conventional to online learning, thus created several risks that need to be addressed through risk management that is targeted, effective and beneficial for students and teachers. This study used quantitative methods with data collection techniques in the form of questionnaires and literature studies. The data was obtained by taking a sampling of 14 teachers at SDN 12 Cawang and measuring the Likert scale on the questionnaires distributed. The results of the Likert scale measurement are then processed into information and combined with the results of a literature study to obtain an in-depth analysis. The result of this study was that the covid 19 pandemic has a significant impact on face-to-face learning at SDN 12 Cawang. This impact has two contradictory meanings. Another result was that the implementation of risk management carried out by SDN 12 Cawang has a significant impact on the effectiveness of online learning. The results of the study concluded that the implementation of risk management has a significant effect on the effectiveness of online learning so that it can be a benchmark for implementing sustainable online learning in the future.